Accuracy assessment of go pro hero 3 (Black) camera in underwater environment - Helmholz, Petra; Long, J.; Munsie, T.; Belton, D. (2016)
Modern digital cameras are increasing in quality whilst decreasing in size. In the last decade, a number of waterproof consumer digital cameras (action cameras) have become available, which often cost less than $500. A possible application of such action cameras is in the field of Underwater Photogrammetry. Especially with respect to the fact that with the change of the medium to below water can in turn counteract the distortions present. The goal of this paper is to investigate the suitability of such action cameras for underwater photogrammetric applications focusing on the stability of the camera and the accuracy of the derived coordinates for possible photogrammetric applications. For this paper a series of image sequences was capture in a water tank. A calibration frame was placed in the water tank allowing the calibration of the camera and the validation of the measurements using check points. The accuracy assessment covered three test sets operating three GoPro sports cameras of the same model (Hero 3 black). The test set included the handling of the camera in a controlled manner where the camera was only dunked into the water tank using 7MP and 12MP resolution and a rough handling where the camera was shaken as well as being removed from the waterproof case using 12MP resolution. The tests showed that the camera stability was given with a maximum standard deviation of the camera constant sc of 0.0031mm for 7MB (for an average c of 2.720mm) and 0.0072 mm for 12MB (for an average c of 3.642mm). The residual test of the check points gave for the 7MB test series the largest rms value with only 0.450mm and the largest maximal residual of only 2.5 mm. For the 12MB test series the maximum rms value is 0. 653mm.